2014
DOI: 10.1111/all.12475
|View full text |Cite
|
Sign up to set email alerts
|

First European data from the network of severe allergic reactions (NORA)

Abstract: This pilot phase of a pan-European registry for severe allergic reactions provides for the first time data on anaphylaxis throughout Europe, demonstrates its potential functionality and allows a comparison of symptom patterns, elicitors and treatment habits between referral centres and countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
216
3
14

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(263 citation statements)
references
References 20 publications
30
216
3
14
Order By: Relevance
“…In the network of severe allergic reactions (NORA), a registry with a high representation of Central European cases, hymenoptera sting allergy is the most common cause of anaphylaxis [4]. In the geographical area of the present study, Catalonia, venom allergy is not so frequent.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In the network of severe allergic reactions (NORA), a registry with a high representation of Central European cases, hymenoptera sting allergy is the most common cause of anaphylaxis [4]. In the geographical area of the present study, Catalonia, venom allergy is not so frequent.…”
Section: Discussionmentioning
confidence: 81%
“…Despite these guidelines, the use of adrenaline is still suboptimal [4]. Different potential barriers to the use of adrenaline have been hypothesized and analyzed [5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The remaining patients were tried to locate by consulting registration offices. A modified German anaphylaxis registry questionnaire [3] was sent to their current address as primary research tool, and patients were requested to complete the form. The questionnaire contained questions about re-stings since discontinuation of VIT, culprit insect, frequency, setting, and symptoms of re-stings.…”
Section: Methodsmentioning
confidence: 99%
“…In children, anaphylactic reactions to hymenoptera stings are estimated to occur in 0.4-0.8% [1,2]. Hymenoptera venom allergy accounts for 20.2% of anaphylactic reactions, which is the second leading cause of anaphylaxis in childhood and adolescence after food allergy [3,4]. Golden et al [2,5] showed that up to one third of children with at least moderate systemic reactions do not outgrow their hypersensitivity and require causal treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Food allergy, an IgE antibody-mediated and potentially life-threatening [1] chronic immunological disease, is a significant clinical problem in Europe and appears to have increased within the past years [2]. Based on clinical food challenge data, peanut and soybean are among the most prevalent elicitors of allergic reactions to foods in Europe [3].…”
Section: Introductionmentioning
confidence: 99%